Patterns of intergenerational child protective services involvement - Font, Sarah (Child Abuse Negl, 2019)
BACKGROUND: Prior research on Child Protective Services (CPS) involvement among at-risk youth focuses on their roles as parents perpetrating maltreatment against biological offspring. Given family complexity and assortative partnering, measuring all CPS involvement – as perpetrators and non-offending parents of victims – provides new insight into intergenerational maltreatment patterns. OBJECTIVES: Our objective was to investigate the risk of multiple forms of parent or perpetrator CPS involvement (PP-CPS) by age 25, among those exposed to three forms of adversity in their late teens (at ages 14–17): alleged victim on a CPS investigation, out-of-home care (OHC), and poverty. PARTICIPANTS AND SETTING: We used a sample of 36,475 individuals born in 1990–1991 from the Wisconsin Data Core longitudinal administrative database, and tracked their involvement in CPS, OHC, and the food assistance program (SNAP) over time. Our sample consisted of individuals who, at ages 14–17, met one of the following criteria: were in OHC; had CPS involvement as a victim but no OHC (CPSV group), or received food assistance without CPSV or OHC (SNAP group). METHODS: Using logistic regression, we modeled four forms of PP-CPS involvement: parent-perpetrator, resident parent non-perpetrator, nonresident parent non-perpetrator, and non-biological parent-perpetrator. RESULTS: Predicted risks of any PP-CPS involvement by age 25 were 10 % (SNAP group), 17–22 % (CPSV group), and 26–33 % (OHC group); among OHC youth known to have a biological child, rates exceeded 40 %. The proportion of CPS involvement that involved parent-perpetration varied substantially by sex and adversity type. CONCLUSIONS: Focusing only on intergenerational maltreatment in which the parents are the perpetrators may substantially understate the risk of maltreatment recurring across generations.